Rhythms of relief: perspectives on neurocognitive mechanisms of music interventions in ADHD - Luo, Zhihui; Zhang, Da-Wei (Frontiers in Psychology, 2025)
Attention-deficit/hyperactivity disorder (ADHD) is a prevalent neurodevelopmental disorder characterized by multiple neurocognitive deficits. Research suggests that music interventions, both active and passive, may be an effective complementary method of addressing ADHD challenges. This narrative review discusses seven potential neurocognitive mechanisms through which music interventions may help mitigate or alleviate ADHD symptoms, including executive function enhancement, timing improvement, arousal regulation, default mode network modulation, neural entrainment, affective management, and social bonding facilitation. Our study synthesized evidence from ADHD-specific studies and examined parallels to other populations to identify possible pathways through which music therapy could exert its effect. The paper also discusses the implications of individualized music interventions tailored to specific neurocognitive profiles in ADHD, advocating additional research to refine and optimize these approaches. Overall, music therapy has substantial potential as a complementary treatment for ADHD, offering new avenues for addressing the psychosocial and cognitive aspects of this condition.